INVESTIGATING THE USE OF STUDENT-GENERATED QUESTIONS IN DISCIPLINARY READING PRACTICES IN HIGHER EDUCATION ENVIRONMENTS - Chodkiewicz, Halina; Kiszczak, Anna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
The paper sets out to explore the issue of students’ strategic ability of learning from disciplinary texts in tertiary education settings. While performing reading tasks, students acquire or restructure subject-area knowledge as well as improving conceptual resources and literacy skills indispensable for their academic attainment. The so-called reciprocal reading instruction promotes the adoption of a procedure in which students are required to generate their own text-based questions, then ask and answer them in pairs. The exploratory case study reported in this paper aimed to examine the performance of advanced Polish students of English during ten reciprocal reading sessions, part of a subject-specific course. The analysis of the collected data focused on selected aspects of the students’ question-generating behaviour. Additionally, the data obtained from a semi-structured interview were scrutinized in order to find out how the students evaluated their task performance. The paper finishes with a discussion of the implications of the study for the use of student-generated questions and reciprocal reading tasks in enhancing disciplinary knowledge and academic literacy skills.